Parkinsonism and dystonia: Clinical spectrum and diagnostic clues - Morales-Briceno, Hugo; Fung, Victor S.C.; Bhatia, Kailash P.; Balint, Bettina (Journal of the neurological sciences, 2022)
The links between the two archetypical basal ganglia disorders, dystonia and parkinsonism, are manifold and stem from clinical observations, imaging studies, animal models and genetics. The combination of both, i.e. the syndrome of dystonia-parkinsonism, is not uncommonly seen in movement disorders clinics and has a myriad of different underlying aetiologies, upon which treatment and prognosis depend. Based on a comprehensive literature review, we delineate the clinical spectrum of disorders presenting with dystonia-parkinsonism. The clinical approach depends primarily on the age at onset, associated neurological or systemic symptoms and neuroimaging. The tempo of disease progression, and the response to L-dopa are further important clues to tailor diagnostic approaches that may encompass dopamine transporter imaging, CSF analysis and, last but not least, genetic testing. Later in life, sporadic neurodegenerative conditions are the most frequent cause, but the younger the patient, the more likely the cause is unravelled by the recent advances of molecular genetics that are focus of this review. Here, knowledge of the associated phenotypic spectrum is key to guide genetic testing and interpretation of test results. This article is part of the Special Issue "Parkinsonism across the spectrum of movement disorders and beyond" edited by Joseph Jankovic, Daniel D. Truong and Matteo Bologna. •Dystonia and parkinsonism share common pathophysiological links.•The syndrome of dystonia-parkinsonism has many different aetiologies.•Particularly the spectrum of its genetic aetiologies keeps expanding.